Mixed-sensitivity Ηoo on-blade control - Alotaibi, J.; Morales, R. (My University, 2018)
In this work, we investigate the use of ?oo control design for OBC. The designed methods are tested on a hingeless analytical rotor model of the four-blade Airbus EC-145 helicopter with Active Trailing Edge Flaps (ATEF). In order to enable the application of the control methods, system identification tools are applied to extract two-input two-output Linear-Time-Invariant models at hover, 20, 40, 60, 80 and 100 knots forward flight. Such linear approximations are obtained after the rotor is trimmed with zero trailing edge flapping. The vibration reduction strategy is developed using robust control mixed-sensitivity methods targeting the fixed-frame 4/rev vertical force component with 4/rev 2aps. The strategy is shown to be satisfactory in the sense that vibration mitigation is obtained with the implementation of a single controller operating for all considered forward flight cases. The vibration reduction was 60% in average in terms of the 4/rev component of the vertical hub force and the vibration reduction scheme is not interfering with the trimming of the rotor.